MWCNT/SiO2 Hybrid Nano‐PCM for Ultrafast Solar Cookers: An Experimental Study - T. Sathish; Jayant Giri; R. Saravanan; Zafar Said; Moaz Al‐lehaibi (Engineering Reports)
ABSTRACT The pursuit of sustainable energy solutions is crucial in meeting global sustainable development goals (SDGs). This experimental study explores enhancing a box‐type solar cooker's thermal performance through the integration of a hybrid nano‐enhanced phase change material (PCM). Specifically, multi‐walled carbon nanotubes (MWCNTs) and silicon oxide (SiO2) nanoparticles were incorporated into the PCM at a 2% concentration, with 1% each of MWCNT and SiO2. The hybrid nano‐PCM was meticulously prepared using ultrasonication to ensure optimal dispersion and homogeneity. This innovative approach significantly improved the cooker's efficiency, achieving a peak PCM temperature of 128.9°C, a cooking power of 47.6 W, an average efficiency of 28.5%, and an energy efficiency of 6.2%. Notably, the cooking time was halved, from 36.3 min to just 18 min, demonstrating the ultrafast capabilities of the solar cooker. These findings underscore the potential of the MWCNT/SiO2 hybrid nano‐PCM in revolutionizing solar cooking technology, offering a cost‐effective, environmentally friendly, and highly efficient solution for sustainable energy harvesting.